Pemanfaatan Bahan Dapur melalui Program GEMILANG Gema Ekslusif Masker Kelor dan Bedda - Vividiya Wijayanti, Sofia Anggita Rani, Nur Islamiatul Anisa, Nurul Aini Ma’rifah, Putri Puji Ayu Le (Perkumpulan Dosen Program Hibah Indonesia, 2025)
The GEMILANG (Exclusive Echo of Moringa and Bedda Lotong Masks) program is a community empowerment initiative implemented by PPG Prajabatan (prospective teachers) batch 2 in 2024 at the Rumah Langit Community with the aim of increasing the use of natural ingredients from the kitchen as self-care products that have economic value. This activity focuses on training in making moringa masks and bedda lotong (traditional body scrubs made from spices) that are easy to apply, inexpensive, and have the potential to be developed as superior community products or daily needs. Through a participatory and educational approach, this program encourages the active involvement of groups, especially students and young women, in the production process, packaging, and how to use the product properly before being marketed. The results of the activity showed an increase in students' knowledge and skills in the use of kitchen ingredients that were previously less noticed, as well as the emergence of creative economic initiatives based on local potential. This training can also be useful in adding skills for students in the Rumah Langit community that are not obtained in formal education and can be applied in activities in the formal education environment. Thus, GEMILANG not only strengthens the independence of students but also raises awareness of the importance of environmentally friendly innovation in the utilization of resources derived from kitchen ingredients.Keywords: empowerment, community, moringa mask, bedda lotong, kitchen ingredients, local innovation